Independent and combined associations of maternal and own smoking with adult lung function and COPD. (17th October 2018) - Magnus, Maria C; Henderson, John; Tilling, Kate; Howe, Laura D; Fraser, Abigail
Abstract: Background: Limited evidence suggests that exposure to maternal smoking in utero or early life might be associated with chronic obstructive pulmonary disease (COPD), but whether this is independent of later own smoking remains unclear. Our objective was to examine the independent and combined association of maternal and own smoking with adult lung function and COPD. Methods: We used UK Biobank to examine associations of maternal smoking around delivery, and pack-years of own smoking, with lung function ( n = 502 626) and hospitalization/death from COPD ( n = 433 863). We calculated the additive interaction between maternal and own smoking on the outcomes of interest, and estimated the association with maternal smoking within categories of own smoking. Results: There was no strong evidence that maternal smoking influenced adult lung health among never smokers. Exposure to both maternal and own smoking was associated with lower Forced expiratory volume (FEV1 )/ forced vital capacity (FVC) and greater risk of hospitalization/death from COPD than expected from their independent associations. For FEV1 /FVC, the mean difference according to maternal smoking was –0.02 (–0.06, 0.02), –0.01 (–0.05, 0.03), –0.11 (–0.16, –0.05) and –0.11 (–0.19, –0.04) among women who smoked ≤10, 11–20, 21–30 and >30 pack-years, respectively. The association between maternal smoking and COPD also varied by pack-years of own smoking, with a hazard ratio of 2.25 (1.30, 3.89) for ≤10 years, 1.23 (0.80, 1.89) for 11–20 years, 1.30 (0.85, 2.01) for 21–30 years and 1.14 (0.91, 1.43) for >30 years. Conclusions: Our findings indicate an excess reduction in FEV1 /FVC and risk of COPD due to maternal smoking that is heterogeneous across levels of own smoking.